Outer membrane penetration by (2,3)-methylenepenams. - Chapman, J S (1987)
The penetration of the Escherichia coli outer membrane by two sterically restricted analogs of penicillin G was determined. The analog corresponding to the "open" conformation of penicillin G penetrated faster than the "closed"-form analog did, and both analogs penetrated faster than penicillin G did. The results suggest that the conformation of the beta-lactam nucleus may affect penetrability via the porin-mediated pathway.